Is evolution faster at ecotones? A test using rates and tempo of diet transitions in Neotropical Sigmodontinae (Rodentia, Cricetidae). Issue 24 (16th December 2021) - Luza, André Luís; Maestri, Renan; Debastiani, Vanderlei Júlio; Patterson, Bruce D.; Hartz, Sandra Maria; Duarte, Leandro D. S.
Abstract: We evaluated whether evolution is faster at ecotones as niche shifts may be needed to persist under unstable environment. We mapped diet evolution along the evolutionary history of 350 sigmodontine species. Mapping was used in three new tip‐based metrics of trait evolution – Transition Rates, Stasis Time, and Last Transition Time – which were spatialized at the assemblage level (aTR, aST, aTL). Assemblages were obtained by superimposing range maps on points located at core and ecotone of the 93 South American ecoregions. Using Linear Mixed Models, we tested whether ecotones have species with more changes from the ancestral diet (higher aTR), have maintained the current diet for a shorter time (lower aST), and have more recent transitions to the current diet (lower aLT) than cores. We found lower aTR, and higher aST and aLT at ecotones than at cores. Although ecotones are more heterogeneous, both environmentally and in relation to selection pressures they exert on organisms, ecotone species change little from the ancestral diet as generalist habits are necessary toward feeding in ephemeral environments. The need to incorporate phylogenetic uncertainty in tip‐based metrics was evident from large uncertainty detected. Our study integrates ecology and evolution by analyzing how fast trait evolution is across space. Abstract : We explored whether evolution is faster at ecotone zones by developing three new tip‐based metrics — a species‐specific characterization of trait evolution — and spatializing them at the species‐assemblage level. We showed that evolution's speed — in terms of rates and time of diet transition — varies over space, with ecoregion ecotones having species with fewer transitions from the ancestral diet, longer stasis time of the current diet, and older transition to the current diet than ecoregion cores. Our research provides a formal link between macroecology and macroevolution, which is still rare in the ecological literature.